Policy for Eliminating Extreme Poverty with an Entrepreneurial Ecosystem: A Poverty Reduction Policy Design - Eko Eddya Supriyanto (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2023)
Eliminating extreme poverty is the mandate of the Indonesian constitution. This study's methodology is qualitative, specializing in designing poverty eradication policy analysis as an entrepreneurial ecosystem. Indonesia's extreme poverty condition will be at 1.74% in 2023. The government has created a program to eliminate extreme poverty, which can meet needs from the health aspect in the form of a Healthy Indonesia card, the food aspect in the form of rice for low-income families, and the education aspect in the form of an intelligent Indonesia card. Of these three aspects, there needs to be an aspect so that low-income families continue to get income to meet their living needs and avoid falling into extreme poverty with an entrepreneurial ecosystem in the form of social entrepreneurship. According to the findings of this study, the government may use a Penta-helix partnership model with other stakeholders to tackle the issue of eradicating poverty by 2024 and meet the target of 0%-1% severe poverty elimination.